Early Printed Narrative Literature in Western Europe - Besamusca, Bart; Willaert, Frank; de Bruijn, Elisabeth (De Gruyter, 2020)
The shift from hand-written to printed books left its mark on narrative literature in Western Europe. The essays in this volume address developments in the history of early printed narrative texts as well as publication strategies in a number of vernacular languages. Topics covered include the selection of texts that made it into print, stages in their printed history, textual adaptations, the use of woodcuts and the development of title pages.